2017
DOI: 10.1007/s13300-017-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and the Risk of Bladder Cancer: A Meta-Analysis

Abstract: People with type 2 diabetes are at increased risk of bladder cancer. Pioglitazone is said to increase it further, although published evidence is mixed. We conducted a meta-analysis to determine if any link between the use of pioglitazone and an increased risk of bladder cancer can be found. A comprehensive literature search was conducted through electronic databases as well as registries for data of clinical trials to identify studies that investigate the effect of pioglitazone on bladder cancer in diabetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 52 publications
1
55
0
1
Order By: Relevance
“…200 Finally, mixed results in the literature have been reported about the relationship between thiazolidinediones and bladder cancer, which remains uncertain, although most studies have failed to observe such an association, particularly if low quality studies are excluded. 201 In summary, many general practitioners and specialists remain unaware that pioglitazone has the potential to induce resolution of NASH in~60% of patients, as well as conferring extrahepatic benefits (i.e., reduction of new-onset diabetes or CVD). However, it is likely that its use will continue to increase in patients with NASH to prevent fibrosis progression.…”
Section: Metformin and Pioglitazonementioning
confidence: 99%
“…200 Finally, mixed results in the literature have been reported about the relationship between thiazolidinediones and bladder cancer, which remains uncertain, although most studies have failed to observe such an association, particularly if low quality studies are excluded. 201 In summary, many general practitioners and specialists remain unaware that pioglitazone has the potential to induce resolution of NASH in~60% of patients, as well as conferring extrahepatic benefits (i.e., reduction of new-onset diabetes or CVD). However, it is likely that its use will continue to increase in patients with NASH to prevent fibrosis progression.…”
Section: Metformin and Pioglitazonementioning
confidence: 99%
“…Ten previous systematic reviews or meta-analyses on the association of pioglitazone use with bladder cancer have already been published [1][2][3][4][5][6][7][8][9][10]. Nevertheless, a final word on risk associated with pioglitazone use cannot be given because these studies are flawed by factors that range from improper use of analytical procedures to scarce consideration of time-related and selection biases.…”
Section: Introductionmentioning
confidence: 99%
“…Another, recent meta-analysis conducted by Filipova and colleague reported no link of bladder cancer risk with pioglitazone use, Relative risk; RR = 1.13; 95% CI 0.96-1.33 and HR = 1.07; 95% CI 0.96-1.18), and suggested hypothetically increased risk of bladder malignancy should be attributed to other factors [11].…”
Section: Do We Still Need Pioglitazone For the Management Of Type 2 Dmentioning
confidence: 97%
“…On the other hand, few studies reported no risk of bladder cancer with pioglitazone use [10,11]. For instance, a recent population based cohort study conducted in United Kingdom (UK) generated 689,616 person years of follow-up, during which 622 patients were newly diagnosed as having bladder cancer (crude incidence 90.2 per 100,000 person years).…”
Section: Reviewmentioning
confidence: 99%